2002
DOI: 10.1046/j.1523-1755.2002.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune responsiveness in renal transplant recipients: Mycophenolic acid severely depresses humoral immunity in vivo

Abstract: Immunosuppressive drug treatment with P/CsA inhibits delayed-type hypersensitivity skin reactions to both primary and frequently encountered antigens. Histological studies indicate an effect on ICAM-1 expression, leaving the influx of CD3pos T cells unaffected. Administration of a 10-day course of IgA CD3 mAb does not add profound immunosuppressive effects on the measured parameters. In contrast, addition of treatment with MMF profoundly decreases both primary and secondary humoral immune responsiveness in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 25 publications
(1 reference statement)
8
71
2
3
Order By: Relevance
“…This finding confirms and extends the data from several small series, published in recent years, showing a suppressed humoral immune response in MMF-treated patients (15)(16)(17)27). Nonetheless, in the present study patients on MMF therapy had SP rates after vaccination that ranged from 74 to 88%.…”
Section: Scharpé Et Alsupporting
confidence: 93%
“…This finding confirms and extends the data from several small series, published in recent years, showing a suppressed humoral immune response in MMF-treated patients (15)(16)(17)27). Nonetheless, in the present study patients on MMF therapy had SP rates after vaccination that ranged from 74 to 88%.…”
Section: Scharpé Et Alsupporting
confidence: 93%
“…In recent studies, MMF has been shown to be capable of depressing humoral immunity in renal allograft recipients (20). In the present case, the substitution of MMF for azathioprine was associated with a significant decrease in T lymphocyte-reactive anti-HLA-A11 DSA by FC, but not its complete disappearance.…”
Section: Discussionsupporting
confidence: 44%
“…These data suggest that the presence of HLA antibodies, DS but also NDS, is associated with transplant failure and that their screening is an important tool for the treatment of patients who receive a kidney transplant, as they could help in discriminating between chronic rejection and nonimmune allograft dysfunction. This discrimination could have therapeutic implications and could lead to specific treatment aimed at either inhibiting their production, such as MMF (16) or the CD20 mAb (17), or neutralizing their action, with plasma exchange and/or intravenous Ig (17)(18)(19)(20), that are used with success in acute vascular rejection. …”
Section: Discussionmentioning
confidence: 99%